Concurrent use and association of patient-reported experience and outcome measures in psychiatric and substance use disorder care: a scoping review - Marte Karoline Råberg Kjøllesdal; Marte Karoline Råberg Kjøllesdal; Hilde Hestad Iversen; Lina Harvold Ellingsen-Dalskau (Frontiers in Health Services, 2025)
BackgroundPatient reported experience measures (PREMs) provide patients` perspectives on health care services received, while generic Patient reported outcome measures (PROMs) reflect their subjective well-being or quality of life. The relationship between these measures is not well understood.AimsTo assess concurrent use and relationship of PREMs and PROMs In psychiatric and substance use disorder care, to inform how they best can be used concurrently in measuring quality of care from the patient perspective.MethodsScoping review following Joanna Briggs Institute guidelines and adhering to the PRISMA extension for Scoping Reviews. Searches were carried out in Medline, CINAHL, Web of Science, Cochrane database of systematic reviews, Embase, and APA PsycInfo. Two researchers independently screened all articles published in English or Scandinavian languages and extracted information using a pre-defined template. Refence lists of included articles were screened for additional studies.ResultsFour articles were included, three from psychiatric care and one from substance use disorder treatment. Four different PREMs measures and three generic PROMs measures were used. Each study found PREMs measures to be associated with generic PROMs, but the strength of the associations varied from weak to strong.ConclusionExisting studies suggest that patient reported experiences are related to quality of life and well-being among patients in psychiatric and substance use disorder care. This study highlights a critical gap in the understanding of how PREMs and PROMs may interact in these patient populations. Despite limited research on their concurrent use, our findings offer preliminary insights into their potential to support patient-centred care.